PENGARUH QIGONG EXERCISE TERHADAP KESEIMBANGAN LANSIA DI RSUD CENGKARENG TAHUN 2024 - Lina, Ratu Karel; Trioclarise, Rovika; Syahputra, Mohammad Reza (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
Background: One of the health problems experienced by the elderly is balance problems. In Indonesia, many elderly people have been found with balance problems and this is one of the most common cases among the elderly. Elderly balance disorders can be treated, among other things, with balance exercises that have relatively easier movements, one of which is Qigong Exercise. Qigong exercise originates from China, using a combination of breathing exercises, meditation and movement. Qigong exercise requires minimal musculoskeletal strain and less energy expenditure and can benefit physical ability, physical function, balance, and psychological health. Objective: To determine the effect of Qigong exercise on the balance of elderly people at Cengkareng Regional Hospital in 2024. Methods: This research uses a quasi-experimental type of research with a two group pretest - posttest with control group design. The treatment group received Qigong exercise and elderly gymnastics training, while the control group received gymnastics training from trainers for each group, totaling 10 respondents. The measuring instrument used is the Berg Balance Scale (BBS). Carried out for 4 weeks with a frequency of 2x/week. Result: Wilcoxon test results in the treatment group had a p value of 0.04 (0.05), while the results of the paired sample T-test in the elderly exercise group had a p value of 0.03 (0.05), the results of Mann Whitney - U Qigong Exercise and elderly exercise were 0.01 (0.05). Conclusion: The addition of Qigong Exercise is more effective for improving elderly balance than just elderly exercise